Análisis de las publicaciones de la fanpage El Universo y su impacto en la sociedad, período marzo – mayo 2020 - Nuñez Garcia, Juana Melissa (2020)
This research addressed the issue of the impact of the publications of the Fanpage El Uninverso on society, due to the fact that it has a large number of followers, who in turn share a lot of content on their profiles. The objective of this case study was to analyze and determine how the spread of false news occurs and the consequences it has on society during the March - May 2020 period of that page. For theoretical support, information on the topic of interest was investigated in bibliographic sources. The proposed methodology was the qualitative approach, which was carried out by observing the content; as are the details of the news, participation and user comments. With the socio-critical method it has been resolved that El Uninverso is the parallel reality of the national newspaper El Universo, the structure of the fanpage is similar and they do not keep a very distant relationship, also with respect to the colors and elements of image and text composition They are similar, but the logo they use in their publications is visibly upside down from that of the newspaper. In this way it is determined that the impact it has is that many come to believe the false news that is disseminated, confusing consumers, and in turn giving a bad image to the real and original press medium.